Straightening trajectory of hooked fibers in the fiber transport channel of rotor spinning investigated by fluid solid coupled simulation - Fengyan Li; Dingtiao Zhang; Qianru Wang; Baoming Zhou; Fang Qiu (Scientific Reports)
Abstract The airflow in the transport channel contributes to the accelerated straightening of the hooked fibers, which greatly influences the structural properties of the yarn. To study the straightening process of hooked fiber in the fiber transport channel, Altair EDEM 2022 software was used to establish flexible fiber models, and combined with ANSYS Fluent 2022R1 simulation software, the fluid-solid coupling method was used to simulate the air velocity distribution in the fiber transport channel and the straightening process of the hooked fibers in the airflow field. The numerical simulated air flow is verified by Hagen-Poissuille pipe flow equation. The effects of different fiber transport channels on the straightening of various hooked fibers were discussed. The results show that the straightening effect of leading hooked fiber in the airflow field is better than that of trailing hooked fiber with significant straight. In the case of the fiber transport channel with a circular cross-section outlet, the straightening of trailing hooked fiber can be slightly enhanced. Considering the feeding position of fibers transferred from carding roller to inlet of fiber transport channel, the collision of hooked fibers with the wall influences straightening of hook part or even reduces the straightness. Through the comparision on straightness between simulated and the experimental fibers, it is verified the better straightening of leading hooked fiber in the fiber sliver in the channel. The straightening process of hooked fibers influenced by airflow field and input location of fiber transport channel are simulated, which provides a reference for optimizing fiber transport channel structure and spinning prameters.